The Interdependency Of House Layout, Privacy And Culture From The User-Behavioural Perspective Of Urban Malays - Mohamad Ali, Harlina (2007)

(untitled)
The most fundamental form of traditional architecture is housing, built by ordinary people to accommodate their lives daily needs. Previous studies have shown that these houses provided better congruence between human behaviour and culture. For instance, in traditional Malay house the spatial organization is more flexible as physical separation of space within it is minimal. Low priority is given to personal privacy where emphasis is more on maintaining closeness within the family or intimacy with family. The main priority is towards protecting the privacy of female family members from male guests. Therefore, the segregation of space between the public domain in front and the private domain at the back is very important. This is demonstrated in the serambi (reception area) located in front of the house where the male guests are entertained during social and religious functions.Nowadays, majority of modern housing are mass-produced and inhabitants have little choice but to adapt their lifestyle within the ‘given environment’ regardless of their behavioural needs and cultural background. The spatial organization of modern link house is more formal as there are fixed and enclosed spaces for specific activities. Using scheduled-structured questionnaires, observation and graphic aid during interviews, this research analyzed the perspectives of urban Malays with regards to privacy concept and cultural needs. From the data analysis, many respondents agreed with the re-introduction of the serambi concept in modern housing as a transition zone for entertaining, where it is used to regulate privacy whilst maintaining privacy of family in the main house. It was found that even though intimacy with family is regarded important, there is awareness for personal privacy among the respondents due to the influence of modern housing layout especially about the separation of space for personal activities. The respondents cited that they either try to adapt themselves to the modern housing layout, adjusted the layout accordingly or have the intention to move elsewhere in the future. A spatial analysis of the respondents’ house plans were conducted, which culminated with a proposed prototype of a standard link house layout which best fulfills current privacy and cultural needs of urban Malays.